Advancing Product Management Through Ai and Erp Integration A Cloud-Centric Strategy for Agile Business Operations - Suneel Kumar Mogali (Journal of Informatics Education and Research, 2024)
In today's rapidly evolving business landscape, the integration of Artificial Intelligence (AI) and Enterprise Resource Planning (ERP) systems has emerged as a transformative approach to enhancing product management. This study explores the development of a cloud-centric strategy that leverages AI-driven analytics and ERP capabilities to optimize product lifecycle management, streamline operations, and drive agility in business processes. By integrating AI with ERP systems on cloud platforms, organizations can achieve real-time data processing, predictive insights, and automated workflows, enabling faster decision-making and improved efficiency. The proposed strategy emphasizes a holistic approach to aligning AI technologies with ERP functionalities, focusing on scalability, adaptability, and seamless collaboration across departments. Case studies and industry insights demonstrate the impact of this integration on reducing operational bottlenecks, enhancing customer satisfaction, and fostering innovation in product development. This research provides actionable frameworks for businesses aiming to adopt AI and ERP integration, underscoring the critical role of cloud technologies in shaping the future of agile and resilient product management.